Improving Digital Literacy in Schools: Education Management Strategies to Prepare Students for Global Challenges - Rachma Putri Kasimbara (PT. Anagata Sembagi Education, 2024)
The rapid development of digital technology has changed various aspects of life, including education, making digital literacy an essential competency that students must have to face global challenges. This study aims to explore education management strategies in improving digital literacy in schools to prepare students for global challenges. This research uses a systematic literature review method, which includes analyzing various studies and reports related to the implementation of digital literacy in educational settings. The results show that effective digital literacy policies, integration of technology in the curriculum and training for teachers can improve students' ability to use technology productively and creatively. Recommendations generated from this literature study include the importance of the role of teachers in supporting students' digital literacy, the need for adequate technology facilities in schools, and collaboration between schools and various external institutions to improve the quality of digital literacy. The implication of this research is the importance of developing more targeted and technology-based education policies, in order to answer the growing global challenges